2013
DOI: 10.3807/josk.2013.17.1.001
|View full text |Cite
|
Sign up to set email alerts
|

Study for Improvement of Laser Induced Damage of 1064 nm AR Coatings in Nanosecond Pulse

Abstract: For the conventionally polished fused silica substrate, an around 100 nm depth redeposition polishing layer was formed on the top of surface. Polishing compounds, densely embedded in the redeposition polishing layer were the dominant factor that limited the laser induced damage threshold (LIDT) of transmission elements in nanosecond laser systems. Chemical etching, super-precise polishing and ion beam etching were employed in different ways to eliminate these absorbers from the substrate. After that, Antirefle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The laser-induced damage threshold of optical thin film affects the output energy and service life of the whole laser system. A lot of studies have shown that nano-defects caused by the fabrication of optical thin films are deemed as a potential source affecting the laser damage susceptibility [1][2][3][4][5][6]. It is believed that the laser-induced damage is the coupling damage process of multi-physical fields.…”
Section: Introductionmentioning
confidence: 99%
“…The laser-induced damage threshold of optical thin film affects the output energy and service life of the whole laser system. A lot of studies have shown that nano-defects caused by the fabrication of optical thin films are deemed as a potential source affecting the laser damage susceptibility [1][2][3][4][5][6]. It is believed that the laser-induced damage is the coupling damage process of multi-physical fields.…”
Section: Introductionmentioning
confidence: 99%
“…The laser-induced damage of optical films is a fundamental challenge in the development of high power or highpeak-intensity laser systems such as the American NIF devices, French LMJ instruments and ICF systems [1][2][3][4]. Optical thin film with high laser-induced damage thresholds is a pivotal component in high-power laser system.…”
Section: Introductionmentioning
confidence: 99%